Intangible resources and efficiency. A comparison of Polish and Spanish textile and clothing industry. - Kapelko, Magdalena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The purpose of this paper is to test the hypothesis that there is a positive relationship between intangible resources across firms and the efficiency levels of those firms. This idea is related to the Resource-Based View of the Firm. As an empirical subject we chose the Polish and Spanish textile and clothing industry during the 1998-2001 period, contrasting the transitional and developed countries. We use a non-parametric frontier technique of Data Envelopment Analysis to derive efficiency indices and then relate them with the measure of intangible resources, while we account also for the impact of a firm's age and an industrial activity. The main result of this study supports the hypothesis for the textile and clothing firms in the developed country of Spain, while intangibles proved to be insignificant in explaining the efficiency of companies in the transitional economy of Poland
Argumenta Oeconomica, 2011, Nr 1 (26), s. 73-90
Keywords: textiles; clothing; efficiency; intangible resources; tekstylia; odzież; przemysł odzieżowy; przemysł tekstylny; zasoby niematerialne